Percepções do espaço no medievo islâmico (séc. xiv): o exemplo de ibn khaldun e ibn battuta - Moreira, Beatriz Juana Isabel Bissio Staricco Neiva (2010)
Study of the Islamic values and vision of the world during the Low Middle Ages through the category space, understanding that this does not exist a priori, but in the realm of each cultural and historical experience. The medieval Muslim world was recognized as a unit, whose limits were those of the Islam, as higher reference of cultural, political and social inclusion, and explicitly associated with this civilization s place. Space becomes hierarchical starting with Mecca, in the Arabic Peninsula, a mandatory pilgrimage place. Hence, the journey to the sacred city was a duty of all those following Islam. This is the main reason why this journey had such an important role in the medieval Islamic society, not only concerning religion, but also as a tool to produce knowledge and preserve it through writing. Regarding time, the 14th century was prioritized due to the consulted sources, namely the Muqaddimah (The Prolegomena), the most illustrative work of the historian Ibn Jaldun (1332-1406), and the book Across the Islam, by the traveler Ibn Battuta (1304-1368), memoirs of the over twenty-year voyage across the Muslim domains.